2009
DOI: 10.1080/07359680903263565
|View full text |Cite
|
Sign up to set email alerts
|

The Path of Patient Loyalty and the Role of Doctor Reputation

Abstract: Patient loyalty to doctors is relevant to medical services in which doctor-patient relationships are central and for which competition has increased in recent years. This study aims at understanding the process whereby patients develop loyalty to their doctor and doctor reputation has a moderating role. Based on a randomization of subjects, the study offers and tests an explanation chain representing key variables determining patient loyalty: patient commitment, trust and satisfaction, and doctor reputation. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 42 publications
1
46
0
3
Order By: Relevance
“…4,5,17,18 Previously, it has been reported that trust encourages loyalty. [13][14] In the present study, this appeared essential to creating and maintaining loyalty. It has also been reported that the longer the doctor-patient relationship has been held, the higher is the confidence level.…”
Section: Comparison With Existing Literaturementioning
confidence: 94%
See 1 more Smart Citation
“…4,5,17,18 Previously, it has been reported that trust encourages loyalty. [13][14] In the present study, this appeared essential to creating and maintaining loyalty. It has also been reported that the longer the doctor-patient relationship has been held, the higher is the confidence level.…”
Section: Comparison With Existing Literaturementioning
confidence: 94%
“…The topics addressed were chosen based on data from the literature and test interviews. 2,[4][5][6]9,[13][14][15] About 15 topics were selected (Boxes 1 and 2).Interviews were conducted between March and July 2015 and the interviews were carried out until data sufficiency was confirmed.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…Platonova et al (2008) found that patients remain loyal to the physician if they are satisfied. Satisfaction was long found to enhance trust in service encounters (Ravald & Grönroos, 1996;Torres et al, 2009). In previous studies satisfaction of patients with physicians was also found to be positively related to trust (Anderson & Dedrick, 1990;Geyskens & Steenkamp, 2000;Stieber, 1985).…”
Section: Introductionmentioning
confidence: 87%
“…Trust is a psychological state in which one is confident in good intentions and motives of another (Barber, 1983;Cook & Wall, 1980). Trust in the physician is an antecedent of loyalty to physicians (Ha, Anat, & Longnecker, 2010;Leisen & Hymanb, 2004;Platonova, Kennedy, & Shewchuk, 2008;Safran et al, 2001;Torres, Vasquez-Parraga, & Barra, 2009). In trusting relationships, one party (i.e., a patient) accepts its vulnerability to the other party (i.e., physician) and expects that other party to perform adequately, irrespective of monitoring or controlling by the insurer (Bromiley & Cummings, 1995;Lewicki & Bunker, 1995;Mayer, Davis, & Schoorman, 1995;McAllister, 1995;Mishra, 1996;Moorman, Zaltman, & Deshpande, 1992).…”
Section: Introductionmentioning
confidence: 98%
“…A doctor's reputation positively influences both the patient's trust and satisfaction (Torres, Vasquez-Parraga, & Barra, 2009). …”
Section: Reputationmentioning
confidence: 99%